2022
DOI: 10.1155/2022/2549845
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in T-Cell Subsets and Serum IFN-γ, IL-17, and IgE Levels in Children with Respiratory Syncytial Virus Capillary Bronchitis and Their Clinical Significance

Abstract: Objective. To investigate the changes in T-cell subsets and serum IFN-γ, IL-17, and IgE levels in children with respiratory syncytial virus capillary bronchitis and their clinical significance. Methods. The clinical data of 50 children with respiratory syncytial virus capillary bronchitis admitted to our hospital between July 2020 and June 2021 were retrospectively reviewed, and they were included in the observation group, while 50 children with a healthy physical examination during the same period were chosen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“… 40 As a type 1 cytokine, IFN‐γ exerts an indirect inhibitory effect on Th2 cell differentiation, thereby suppressing IgE synthesis. 41 This could potentially explain the less pronounced increase in IgE levels observed in the IHP group. Th17 cells are known to secrete a variety of cytokines, including IL‐17A and IL‐6, which play crucial roles in neutrophil recruitment, activation, and migration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 40 As a type 1 cytokine, IFN‐γ exerts an indirect inhibitory effect on Th2 cell differentiation, thereby suppressing IgE synthesis. 41 This could potentially explain the less pronounced increase in IgE levels observed in the IHP group. Th17 cells are known to secrete a variety of cytokines, including IL‐17A and IL‐6, which play crucial roles in neutrophil recruitment, activation, and migration.…”
Section: Discussionmentioning
confidence: 99%
“…IFN‐γ has been shown to activate eosinophils through the induction of CD69 expression 40 . As a type 1 cytokine, IFN‐γ exerts an indirect inhibitory effect on Th2 cell differentiation, thereby suppressing IgE synthesis 41 . This could potentially explain the less pronounced increase in IgE levels observed in the IHP group.…”
Section: Discussionmentioning
confidence: 99%
“…Th17/Th1 cells can secrete both IL-17A and IFN-g as potentially pathogenic Th17 cells (41,42). An increasing number of studies have revealed the clinical relevance of Th17/Th1 cells and IL-17A and IFN-g in patients with immune diseases such as autoimmune diseases (43,44) and many other intestinal immune diseases (12)(13)(14)(15). Given the results of the present study, whether the elevated levels of IFN-g and IL-17A in saliva are related to Th17/Th1 cells and whether Th17/Th1 cells contribute to FA require further study.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%